Survival of Isolated Probiotic Yeast Strains from Kefir Towards Bile and Acidic Environments - Azhar, M. A.; M.S., Munaim (International Scientific Organization, 2023)
Probiotic yeast is one of the most important probiotics in kefir drinks and has been shown to have positive effects on gut health. The abundance of probiotic yeast strains in kefir drinks provides an opportunity to identify potential probiotic yeast as dietary supplements or functional food. Currently, yeast products are not as widely available as bacterial strains, but this is expected to change in the near future. Probiotics must resist acid and bile and adhere to the intestinal surface to thrive and colonise the gastrointestinal tract. Therefore, this study aims to investigate the ability of locally isolated yeast strains to resist acid and bile stress. An in vitro experiment was conducted using sample strains isolated from kefir beverages such as Kodamaea ohmeri, Kazachstania unispora, Saccharomyces cerevisiae, and Saccharomyces boulardii. Acid tolerance was determined by varying the pH of YEPD broth from 2 to 7, and bile tolerance was determined using YEPD broth with bile salt concentrations of 0%, 0.3%, 0.5%, and 1%. The study findings show that most isolated yeast strains survive acidic and bile environments. They were able to survive pH 3 for 24 hours (about log 6 CFU/mL). Only Saccharomyces boulardii and Kodamea ohmeri could survive for 24 hours in 1% bile acid (log 6.41 to log 7.34 CFU/mL), whereas all strains survive in 0.3% bile salt (log 3.42 to 8.95 CFU/mL). This study shows that all isolated yeasts have remarkable potential probiotic properties.